Tourniquet-induced ischaemia during total knee arthroplasty results in higher proteolytic activities within vastus medialis cells: a randomized clinical trial - Jawhar, Ahmed; Hermanns, Stephan; Ponelies, Norbert; Obertacke, Udo; Röhl, Henning (Knee surgery, sports traumatology, arthroscopy, 2016)
Purpose Recent data suggest diminished post-operative quadriceps muscle strength after tourniquet application during total knee arthroplasty (TKA). The metabolic effects of the commonly utilized intraoperative tourniquet with consecutive ischaemia on the skeletal muscle cells were unknown. Ubiquitin proteasome system represents one of the main pathways involved in muscle protein breakdown contributing to muscle atrophy. Therefore, the purpose of the present study was to quantify the acute effects of the tourniquet application during TKA on the (1) concentrations of free/conjugated ubiquitin, (2) total ubiquitin-protein ligase activity, (3) proteasome-dependent and (4) proteasome-independent peptidase activities in the cells of vastus medialis.MethodsThe randomized, controlled, monocentric trial included 34 patients scheduled to undergo primary TKA. Each patient was randomly assigned to the tourniquet (n = 17) or non-tourniquet group (n = 17) after receiving a written consent. Muscle biopsies of (5 × 5 × 5 mm) 125 mm3 were obtained from vastus medialis immediately after performing the surgical approach and exactly 60 min later. After preparation of the muscle tissue specimen, the concentrations of the free/conjugated ubiquitin (Ub) were measured by western blot analyses. The ubiquitination was determined as biotinylated Ub incorporated into the sum of the cytosolic proteins and expressed as total ubiquitin-protein ligase activity (tUbPL). The quantification of the proteasome-dependent and proteasome-independent peptidase activities was performed with peptidase assays.ResultsTourniquet application did not influence the concentration of the free/conjugated Ub. There were no differences in tUbPL activities between groups and time points. Tourniquet-induced ischaemia resulted in statistically significant higher proteasome-dependent (caspase-like p = 0.0034; chymotryptic-like p = 0.0013; tryptic-like p = 0.0036) and proteasome-independent (caspase-like p = 0.03; chymotryptic-like p = 0.0001; tryptic-like p = 0.0062) peptidase activities.ConclusionTourniquet application did not affect the free/conjugated Ub as well as tUbPL significantly, emphasizing the sophisticated regulation of ubiquitination. The proteasome-dependent peptidase activities were significantly upregulated during tourniquet application, suggesting an increase in protein degradation, which in turn might explain the skeletal muscle atrophy occurring after TKA. These findings add further knowledge and should raise the awareness of surgeons about the effects of tourniquet-induced ischaemia at the molecular level. Additional high-quality research may be warranted to examine the short- and long-term clinical significance of the present data.Level of evidenceI.